An algebra problem by Coby Tran

Algebra Level 4

64 k = 1 k 2 ( 3 k + 3 4 k + 4 ) \large 64\sum_{k=1}^{\infty}k^2\left(\frac{3^{k+3}}{4^{k+4}}\right) Compute the sum above.


The answer is 567.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Guilherme Niedu
Feb 21, 2017

It's possible to note that:

k = 1 x k = x 1 x \large \displaystyle \sum_{k=1}^{\infty} x^k = \frac{x}{1-x} .

Differentiating with respect to x x and multiplying by x x one gets:

k = 1 k x k = x ( 1 x ) 2 \large \displaystyle \sum_{k=1}^{\infty} k x^k = \frac{x}{(1-x)^2} .

Doing it again:

k = 1 k 2 x k = x ( 1 x 2 ) ( 1 x ) 4 \large \displaystyle \color{#20A900} \sum_{k=1}^{\infty} k^2 x^k = \frac{x(1-x^2)}{(1-x)^4} .

So:

64 k = 1 k 2 3 k + 3 4 k + 4 \large \displaystyle 64 \sum_{k=1}^{\infty} k^2 \frac{3^{k+3}}{4^{k+4}} .

Becomes

= 64 27 256 k = 1 k 2 ( 3 4 ) k \large \displaystyle = 64\cdot \frac{27}{256} \sum_{k=1}^{\infty} k^2 \Big( \frac34 \Big)^k .

= 27 4 ( 3 / 4 ) ( 1 ( 3 / 4 ) 2 ) ( 1 3 / 4 ) 4 \large \displaystyle = \frac{27}{4} \cdot \frac{(3/4)(1 - (3/4)^2)}{(1 - 3/4)^4}

= 27 4 3 4 7 16 256 \large \displaystyle = \frac{27}{4} \cdot \frac34 \cdot \frac{7}{16} \cdot 256

= 567 \large \displaystyle \color{#3D99F6} = \fbox{567}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...